Environmental & architectural phenomenology. Vol. 12, issue 2 - (:unkn) unknown (Kansas State University. Architecture Department, 2001)
Vol. 12, No. 2, Spring 2001 (includes “items of interest,” “citations received,” book commentary of Ingrid Leman Stefanovic's Safeguarding Our Common Future, and three passages from Christain Norberg-Schulz's Architecture: Presence, Language, Place).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals